The political transformation of Gulf tribal states : elitism and the social contract in Kuwait, Bahrain and Dubai, 1918-1970s - Yanai, Shaul (Sussex, England : Sussex Academic Press, 2014)
This study details how the reform movements and attempts to establish parliamentary institutions in the Persian Gulf states of Kuwait, Bahrain, and Dubai between the First World War and the independent era of the 1970s represented a milestone in the history of the region, creating a legacy for future generations, but was a unique transition in the Arab world. An important work to understanding the history of the Persian Gulf states, the book illustrates how, as this new political and social order evolved, ideas of national struggle and national rights penetrated Gulf societies. Gulf citizens w.
The Failure of the Kuwaiti Constitutional CouncilChapter 8: Dubai's Legislative Council, 1938-1940; Institutionalization of the Tribal State; The Power Struggle between the Legislative Council and Sheikh Sa'id al-Maktoum; The Violent Dissolution of the Legislative Council; Explaining the Legislative Council's Failure; Part IV: Parliamentarianism in the Age of Independence; Introduction to Part IV; Chapter 9: The Development of a New Political Culture; Conflicts within the Kuwaiti al-Sabah Family Prior to Independence; A New Political Culture in the al-Sabah family.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Social change -- Persian Gulf States -- History -- 20th century; Political culture -- Persian Gulf States -- History -- 20th century; Tribal government -- Persian Gulf States -- History -- 20th century; Elite (Social sciences) -- Persian Gulf States -- History -- 20th century; Social contract -- History -- 20th century; Persian Gulf States -- Politics and government -- 20th century; Kuwait -- Politics and government -- 20th century; Bahrain -- Politics and government -- 20th century; Dubayy (United Arab Emirates : Emirate) -- Politics and government -- 20th century; Gouvernement tribal -- États du golfe Persique -- Histoire -- 20e siècle.; Élite (Sciences sociales) -- États du golfe Persique -- Histoire -- 20e siècle.; Contrat social -- Histoire -- 20e siècle.; HISTORY -- Middle East -- General; Elite (Social sciences); Political culture; Politics and government; Social change; Social contract; Tribal government; Bahrain; Kuwait; Persian Gulf States; United Arab Emirates -- Dubayy (Emirate); 1900-1999; History